Behavioral Ecology of Pollinator Species (Zoological Archives: An International Journal, 2026)
Pollinators are declining globally, with cascading consequences for wild plant reproduction and agricultural foodproduction, yet the behavioural ecology mechanisms underlying pollinator foraging decisions, inter-specific competition,and habitat use remain incompletely characterised across landscape gradients relevant to European agriculturalsystems. This study investigated the behavioural ecology of six wild bee species (Bombus terrestris, Bombus lapidarius,Apis mellifera, Andrena fulva, Osmia bicornis, and Halictus rubicundus) and three hoverfly species (Episyrphus balteatus,Eristalis tenax, Syrphus ribesii) across 42 sites spanning a flower-resource gradient from flower-rich semi-naturalgrasslands to resource-poor intensive arable landscapes in central Italy and southern France. Focal animal behaviouralobservations (12,840 individual foraging bouts, 2020-2023), RFID-tagged forager tracking (284 B. terrestris colonies;8,420,000 foraging events), and floral resource mapping (18 plant families quantified at 50 m grid) were combined toquantify: (i) inter-specific foraging niche partitioning; (ii) floral constancy and flower-handling efficiency; (iii) foragingdistance and habitat use in relation to landscape context; and (iv) inter-specific competition intensity. Resourcepartitioning was significant across all species pairs tested (Pianka's niche overlap O < 0.40 in 18 of 28 pairs), withpartitioning primarily by flower species identity rather than plant family or foraging height. Bumble bee foraging distanceswere 2.84-fold greater in resource-poor (mean 1,284 +/- 284 m) than resource-rich landscapes (mean 448 +/- 84 m).Flower-handling time was 1.84-fold longer at low flower density sites, consistent with information search costs increasingwith decreasing resource density. These findings identify flower species diversity -- rather than flower abundance alone -as the primary determinant of pollinator behavioural ecology and foraging efficiency.